A comprehensive Investigation of Drought and Standard Precipitation Index (SPI) - Mr. Gajanan H. Chavhan, Mangesh S. Deshpande, Rajesh M. Jalnekar (Mathematical Statistician and Engineering Applications, 2023)
Drought is a prolonged period of below-average precipitation, leading to a shortage of water for various uses and leading to negative impacts on natural and human systems. Drought can also be defined as a deficiency in the water supply whether atmospheric (precipitation), surface water or ground water sources. It can be categorized into meteorological, agricultural, and hydrological drought depending on the sector and the time scale considered. Drought can have severe impacts on agriculture, ecosystems, and communities, and can lead to food and water shortages, wildfires, and economic losses. Drought is a slow-onset disaster, and its impacts can accumulate over time, making it difficult to predict and manage.